Advancements in Expanded Clay Manufacturing Using "Clay-Desert Sand-Oil Sludge" Sludge Composite Materials: Kemajuan dalam Pembuatan Tanah Liat yang Diperluas Menggunakan Bahan Komposit "Tanah Liat-Pasir Gurun Pasir-Lumpur Minyak" - Abdibekovna, Narmanova Roza (Indonesian Journal of Innovation Studies, 2024)
This study explores the development of resource-saving expanded clay technology utilizing underutilized clay raw materials and oil extraction waste. Traditional expanded clay production is energy-intensive and often employs high-quality clay; however, our research identifies technological modes and parameters for producing expanded clay through plastic molding, incorporating substandard raw materials and oil sludge. This method eliminates the need for costly energy-releasing additives and reduces energy costs associated with drying and firing by 25-30%. The research aims to demonstrate the feasibility of this novel production technique in the Republic of Kazakhstan, considering the local availability of raw materials, energy resources, and regional demand for thermal insulation materials in industrial and civil construction. Our findings suggest that integrating 'Desert Sand-Oil Sludge' into the batch composition can effectively produce granulated porous thermal insulation material, aligning with the region's development strategy and offering significant economic and environmental benefits. Highlights: Resource Utilization: Uses oil waste and substandard clay to produce expanded clay, reducing reliance on high-quality materials. Energy Savings: Cuts energy costs for production by 25-30% through innovative processing. Regional Benefit: Aligns with Kazakhstan's strategy by utilizing local resources and supporting construction needs. Keywords: Expanded Clay, Oil Sludge, Desert Sand